The manifestation of diseases and phytophages of weeds associated with the cultivation of flax, the possibility of their use as biological plant protection agents - Savoskina O.A.; Chebanenko S.I.; Zavertkin I.A.; Shitikova A.V.; Kudryavtsev N.A. (BIO Web of Conferences, 2023)
Materials on the study of diseases and phytophages of weeds associated with flax cultivation and on the results of their use in biological plant protection are presented. It has been established that the developed biopreparation (a mixture of inoculum of smut / urocystosis / couch-grass (the disease causative agent Urocystis agropyri / P./ S.) and rust /puccinia / yellow thistle (pathogen Puccinia suaveollens /Pers./) reduces the sowings contamination with these weeds. When sowing flax in regions new to this crop (for example, in the Tula region), phytophages unusual for this crop (for example, rapeseed flea) can significantly damage not flax, but cruciferous weeds. Studies have established that Cirsium setosum in flax sowings is often affected by a specific rust /puccinia / (pathogen Puccinia suaveollens /Pers./ R. [= P. obtegens /Lk./ Tul.]), causing on average about 20% of cases of its destruction without the formation of seeds.